Molecular composition and gas-particle partitioning of indoor cooking aerosol: Insights from a FIGAERO-CIMS and kinetic aerosol modeling. Issue 12 (1st November 2022) - Masoud, Catherine G.; Li, Ying; Wang, Dongyu S.; Katz, Erin F.; DeCarlo, Peter F.; Farmer, Delphine K.; Vance, Marina E.; Shiraiwa, Manabu; Hildebrandt Ruiz, Lea
Abstract: Organic aerosol emitted from cooking is a major concern for indoor air quality. During the House Observations of Microbial and Environmental Chemistry (HOMEChem) campaign, we simulated cooking, cleaning and occupancy activities in a realistic residential setting and measured resulting gas- and particle-phase emissions using a High-Resolution Time-of-Flight Chemical Ionization Mass Spectrometer with a Filter Inlet for Gases and Aerosols (FIGAERO-HR-ToF-CIMS). We identified ∼480 molecular formulas for compounds emitted on cooking-centered days and attributed them to potential sources including cooking, commercial, personal care products, and occupancy. Compounds with molecular formulas containing carbon, hydrogen, and oxygen atoms only (CHO group) composed most of the CIMS-measured molar fraction at 74-85%, with nitrogen-containing molecular formulas (CHNO group) being the second largest contributor (12-19%). We investigated the volatility of identified species based on FIGAERO-CIMS data in three ways: (1) using the maximum desorption temperature from one-dimensional thermograms, Tmax, (2) calculating gas-particle partitioning, Fp, (3) using a molecular corridor parameterization to estimate saturation concentrations based on molecular formulas. We used the kinetic multi-layer model of gas-particle interactions in aerosols and clouds (KM-GAP) to calculate equilibration timescales and found that under sampling conditions ( T  = 323 K), it can take up to 14 seconds for equilibrium conditions to be met, whereas sampling residence times are approximately 3 seconds. The chemical diversity and wide range of volatilities of species sampled during cooking-centered events highlight the importance of understanding aerosol emissions and partitioning in indoor spaces where people spend most of their time.